Growth Factors Release From Concentrated Growth Factors: Effect of β-Tricalcium Phosphate Addition. Issue 8 (November 2018) - Bonazza, Veronica; Hajistilly, Christopher; Patel, Dinker; Patel, Jatan; Woo, Rita; Cocchi, Marco Angelo; Buffoli, Barbara; Lancini, Davide; Gheno, Ezio; Rezzani, Rita; Jahanzeb, Sadia; Hunnisett, Adrian; et al.
Abstract : Background: Platelet concentrates represent a new approach to improve tissue regeneration and can be used alone or together with autogenous bone, recombinant human growth factors, and/or other biomaterials, to enhance tissue regeneration. Among platelet concentrates, concentrated growth factors (CGFs) exhibit an interesting clinical and biotechnological application potential. Objective: The aim of this study was to evaluate the in vitro release of 4 growth factors (bone morphogenetic proteins [BMP] -2, BMP-7, transforming growth factor [TGF] -β1, and insulin-like growth factor [IGF] -1) by the enzyme-linked immunosorbent assay (ELISA) technique, in CGFs mixed or not with β-tricalcium phosphate (β-TCP), using or not the Round-up device, at different times. Methods: CGFs were obtained from healthy volunteers, mixed or not with β-TCP, using or not the Round-up device. The release of 4 growth factors from these CGFs was then measured at 5 hours, 1, 3, 6, and 8 days, using the ELISA assay. Results: Comparison of the results obtained with those achieved for CGFs alone showed that BMP2 and BMP-7 release, significantly increased in CGFs mixed with Round-up and β-TCP, TGF-β1 release was similar to CGFs alone, whereas IG-1 release was lower compared with CGFs alone. Conclusion: The present data suggest that β-TCP addition to CGF could enhance and improve tissue regeneration, especially bone regeneration, increasing the release of some growth factors that play an important role in osteogenesis.